Study of aortic valve using multi slice computed tomography in patients presenting with chest pain - Mubarra Nasir; Hafiz Muhammad Shafique; Farhan Tuyyab; Rehana Khadim (Journal of the Pakistan Medical Association, 2021)
Objective: To determine aortic root dimensions in younger patients presenting with chest pain. Study Design: Descriptive cross sectional study Study Setting: CT Angiography Department of Armed Forces Institute of Cardiology & National Institute of Heart Diseases, Rawalpindi. Duration of study:6 months (from 12th September 2018 to 11th March 2019) Methods: MSCT angiography was performed over all the patients who met the inclusion and exclusion criteria after written informed consent .MSCT acquisition was performed in a single breath-hold of about 5–10 seconds, ECG gated synchronized data acquisition with 60-100ml contrast was done.Multiphase data sets were reconstructed followed by data analysis. Required measurements were recorded with software caliper and tracer. All data were analyzed in SPSS 23. Results: Recruited in the study were a total of 330 patients who fulfilled the inclusion criteria. Mean age (years) was45.5±7.9 and there were 236 (71.5%) male and 94 (28.5%) female patients in the study. Bicuspid aortic valve was found in 0.9%(n=3) of population whereas 99.1%(n=320) were tricuspid. The mean aortic valve area was 4.01±0.70cm2, mean aortic annular size was 21.9±2.37mm,Sinotubular junction diameter on average was found to 23.9±3.45mm, and mean sinotubular junction height was 21.09±2.77mm.The diameter at sinuses of Valsalva was found to be 33.0±3.99mm. Conclusion: The mean aortic root dimensions and general morphology of aortic valve was determined in our population to establish normal reference values, which will later help in therapeutic strategies in patients suffering from aortic valve disease. MSCT was utilized in the assessment of these parameters, also proves Continuous...